Frequency of Chronic Kidney Disease (CKD) in Diabetic Cancer Patients - Awan, Mishal; Arslan, Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of chronic kidney disease in diabetes mellitus associated cancer patients. Design of Study: Cross-sectional study. Place and Study Duration: Department of Medicine, Shaukat Khanum Memorial Hospital and Research centre, Lahore. From January 2024 to December 2024. Methodology: A total of 96 individuals, both male and female, aged 18 to 60, with diabetes and cancer were included. Cases involving known non diabetic patients and patients with type 1 diabetes were excluded. The fundamental variables include age (in years), gender, and the type of cancer were noted down via a patient information sheet. Diabetes, hypertension, glomerulonephritis, or genetic predisposition are some of the underlying factors that can lead to impaired waste and fluid regulation in the body. Kidney damage indicators such as albuminuria and a persistent decline in GFR below 60 mL/min/1.73 m² are indicators of CKD, which is characterized by a progressive loss of kidney function. Results: The study's participants ranged in age from 18 to 60, with a mean age of 47.30 ± 8.64 years. The majority of the 71 patients, or 73.96%, were in the 41–60 age range. With a male to female ratio of 1.7:1, 61 (63.54%) of the 96 patients were men and 35 (36.46%) were women. In our investigation, the average duration of DM was 5.86 ± 2.65 years. 37 (38.54%) of the cancer patients in our study who had diabetes mellitus also had chronic renal disease. Conclusion: According to the study's findings, cancer patients with diabetes mellitus have a very high prevalence of chronic renal disease.